Review of Edwin Malachi Vethamani’s Have I Got Something To Tell You (2024): A Celebration of Marginalised Identities - Samarawickrama, Enakshi (SARE: Southeast Asian Review of English, 2024)
Malachi Edwin Vethamani’s latest short story collection Have I Got Something to Tell You (2024) published by Penguin Books gives voice to the marginalised and insight into their internal worlds. As with his other collections, both short stories and poetry, Vethamani writes about complex human emotions. Consisting of a mix of old and new short stories, this collection explores a range of topics from gender and sexuality to race with a mix of wit and Vethamani’s characteristic minimalist writing style, peopled with memorable, intriguing, and well-written characters.